Hubungan Kepatuhan Minum Obat Antihipertensi Terhadap Kualitas Hidup Pada Pasien Hipertensi Di Provinsi Jawa Tengah - Dedy Frianto; Annisa Fitriyani; Dinda Dinanti; Kartika Sari; Maulida Mutiah; Muhammad Zein (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Basically the purpose of this study was to observe the description of adherence to taking antihypertensive medication with quality of life in hypertensive patients in Central Java Province. The method used in this study is a quantitative method with a cross sectional design. Data were obtained by using a knowledge questionnaire for antihypertensive treatment and the